Nuprl Lemma : ppcc-test4
∀f:ℤ ⟶ ℤ
  ∀[Q,P:ℤ ⟶ ℤ ⟶ ℙ].
    ((∀a,b:ℤ.  (Q[f[a];b] 
⇐⇒ P[a;f[b]]))
    
⇒ Trans(ℤ;a,b.P[a;b])
    
⇒ (∀z,w:𝔹.
          ∀a,b,c,d,e:ℤ. ∀x:{z:ℤ| f[(z + 1) - 1] = d ∈ ℤ} .
            ((f[(b + 2) - 2] = if (w ∨bz) ∧b (c =z x) then e + 1 else f[b] fi  ∈ ℤ) c∧ P[a;a + 1])
            
⇒ P[(a + a) - a;c]
            
⇒ (∀x:ℤ × ℤ. Q[fst(x);b] 
⇒ P[snd(x);e + 1] supposing x = <d, a> ∈ (ℤ × ℤ)) 
            supposing <<c, a>, e> = <<x, a>, e> ∈ (ℤ × ℤ × ℤ) 
          supposing (↑z) ∧ (¬↑w)))
Proof
Definitions occuring in Statement : 
trans: Trans(T;x,y.E[x; y])
, 
bor: p ∨bq
, 
band: p ∧b q
, 
assert: ↑b
, 
ifthenelse: if b then t else f fi 
, 
eq_int: (i =z j)
, 
bool: 𝔹
, 
uimplies: b supposing a
, 
uall: ∀[x:A]. B[x]
, 
cand: A c∧ B
, 
prop: ℙ
, 
so_apply: x[s1;s2]
, 
so_apply: x[s]
, 
pi1: fst(t)
, 
pi2: snd(t)
, 
all: ∀x:A. B[x]
, 
iff: P 
⇐⇒ Q
, 
not: ¬A
, 
implies: P 
⇒ Q
, 
and: P ∧ Q
, 
set: {x:A| B[x]} 
, 
function: x:A ⟶ B[x]
, 
pair: <a, b>
, 
product: x:A × B[x]
, 
subtract: n - m
, 
add: n + m
, 
natural_number: $n
, 
int: ℤ
, 
equal: s = t ∈ T
Definitions unfolded in proof : 
all: ∀x:A. B[x]
, 
uall: ∀[x:A]. B[x]
, 
implies: P 
⇒ Q
, 
uimplies: b supposing a
, 
member: t ∈ T
, 
and: P ∧ Q
, 
not: ¬A
, 
false: False
, 
so_apply: x[s1;s2]
, 
pi1: fst(t)
, 
subtype_rel: A ⊆r B
, 
so_lambda: λ2x.t[x]
, 
so_apply: x[s]
, 
cand: A c∧ B
, 
bool: 𝔹
, 
unit: Unit
, 
it: ⋅
, 
btrue: tt
, 
uiff: uiff(P;Q)
, 
bor: p ∨bq
, 
ifthenelse: if b then t else f fi 
, 
band: p ∧b q
, 
bfalse: ff
, 
exists: ∃x:A. B[x]
, 
or: P ∨ Q
, 
sq_type: SQType(T)
, 
guard: {T}
, 
bnot: ¬bb
, 
assert: ↑b
, 
prop: ℙ
, 
so_lambda: λ2x y.t[x; y]
, 
iff: P 
⇐⇒ Q
, 
rev_implies: P 
⇐ Q
, 
pi2: snd(t)
, 
squash: ↓T
, 
true: True
, 
trans: Trans(T;x,y.E[x; y])
Lemmas referenced : 
assert_witness, 
product_subtype_base, 
int_subtype_base, 
subtract_wf, 
eqtt_to_assert, 
eqff_to_assert, 
bool_cases_sqequal, 
subtype_base_sq, 
bool_subtype_base, 
assert-bnot, 
eq_int_wf, 
set_subtype_base, 
equal_wf, 
istype-int, 
assert_wf, 
istype-void, 
bool_wf, 
trans_wf, 
add-subtract-cancel, 
squash_wf, 
true_wf, 
istype-universe, 
subtype_rel_self, 
iff_weakening_equal, 
eq_int_eq_true, 
btrue_wf, 
iff_imp_equal_bool, 
bfalse_wf, 
istype-assert, 
bor_wf, 
iff_weakening_uiff, 
or_wf, 
false_wf, 
assert_of_bor, 
iff_transitivity, 
equal-wf-base, 
assert_of_band, 
and_functionality_wrt_uiff3, 
assert_of_eq_int, 
ite_rw_true, 
pi2_wf, 
pi1_wf, 
band_wf, 
ifthenelse_wf
Rules used in proof : 
sqequalSubstitution, 
sqequalTransitivity, 
computationStep, 
sqequalReflexivity, 
lambdaFormation_alt, 
isect_memberFormation_alt, 
cut, 
introduction, 
sqequalRule, 
sqequalHypSubstitution, 
productElimination, 
thin, 
independent_pairEquality, 
extract_by_obid, 
isectElimination, 
hypothesisEquality, 
independent_functionElimination, 
hypothesis, 
lambdaEquality_alt, 
dependent_functionElimination, 
voidElimination, 
functionIsTypeImplies, 
inhabitedIsType, 
rename, 
axiomEquality, 
universeIsType, 
applyEquality, 
because_Cache, 
equalityIsType4, 
baseApply, 
closedConclusion, 
baseClosed, 
intEquality, 
independent_isectElimination, 
productIsType, 
addEquality, 
natural_numberEquality, 
unionElimination, 
equalityElimination, 
equalityTransitivity, 
equalitySymmetry, 
dependent_pairFormation_alt, 
equalityIsType1, 
promote_hyp, 
instantiate, 
setElimination, 
setIsType, 
functionIsType, 
universeEquality, 
imageElimination, 
imageMemberEquality, 
productEquality, 
independent_pairFormation, 
unionIsType, 
inrFormation_alt, 
isect_memberEquality_alt, 
cumulativity, 
hyp_replacement, 
dependent_set_memberEquality_alt, 
equalityIsType3, 
applyLambdaEquality
Latex:
\mforall{}f:\mBbbZ{}  {}\mrightarrow{}  \mBbbZ{}
    \mforall{}[Q,P:\mBbbZ{}  {}\mrightarrow{}  \mBbbZ{}  {}\mrightarrow{}  \mBbbP{}].
        ((\mforall{}a,b:\mBbbZ{}.    (Q[f[a];b]  \mLeftarrow{}{}\mRightarrow{}  P[a;f[b]]))
        {}\mRightarrow{}  Trans(\mBbbZ{};a,b.P[a;b])
        {}\mRightarrow{}  (\mforall{}z,w:\mBbbB{}.
                    \mforall{}a,b,c,d,e:\mBbbZ{}.  \mforall{}x:\{z:\mBbbZ{}|  f[(z  +  1)  -  1]  =  d\}  .
                        ((f[(b  +  2)  -  2]  =  if  (w  \mvee{}\msubb{}z)  \mwedge{}\msubb{}  (c  =\msubz{}  x)  then  e  +  1  else  f[b]  fi  )  c\mwedge{}  P[a;a  +  1])
                        {}\mRightarrow{}  P[(a  +  a)  -  a;c]
                        {}\mRightarrow{}  (\mforall{}x:\mBbbZ{}  \mtimes{}  \mBbbZ{}.  Q[fst(x);b]  {}\mRightarrow{}  P[snd(x);e  +  1]  supposing  x  =  <d,  a>) 
                        supposing  <<c,  a>,  e>  =  <<x,  a>,  e> 
                    supposing  (\muparrow{}z)  \mwedge{}  (\mneg{}\muparrow{}w)))
Date html generated:
2019_10_15-AM-11_06_43
Last ObjectModification:
2018_10_12-AM-10_17_24
Theory : general
Home
Index